Spatially variable hydrologic impact and biomass production tradeoffs associated with Eucalyptus (E. grandis) cultivation for biofuel production in Entre Rios, Argentina. Issue 5 (16th March 2021) - Heidari, Azad; Watkins, David; Mayer, Alex; Propato, Tamara; Verón, Santiago; de Abelleyra, Diego
Abstract: Climate change and energy security promote using renewable sources of energy such as biofuels. High woody biomass production achieved from short‐rotation intensive plantations is a strategy that is increasing in many parts of the world. However, broad expansion of bioenergy feedstock production may have significant environmental consequences. This study investigates the watershed‐scale hydrological impacts of  Eucalyptus ( E .  grandis ) plantations for energy production in a humid subtropical watershed in Entre Rios province, Argentina. A Soil and Water Assessment Tool (SWAT) model was calibrated and validated for streamflow, leaf area index (LAI), and biomass production cycles. The model was used to simulate various  Eucalyptus plantation scenarios that followed physically based rules for land use conversion (in various extents and locations in the watershed) to study hydrological effects, biomass production, and the green water footprint of energy production. SWAT simulations indicated that the most limiting factor for plant growth was shallow soils causing seasonal water stress. This resulted in a wide range of biomass productivity throughout the watershed. An optimization algorithm was developed to find the best location for  Eucalyptus development regarding highest productivity with least water impact.  E .  grandis plantations had higher evapotranspiration rates compared to existing terrestrial land cover classes; therefore, intensive land use conversion to  E .  grandis caused a decline in streamflow, with January through March being the most affected months. October was the least‐affected month hydrologically, since high rainfall rates overcame the canopy interception and higher ET rates of  E .  grandis in this month. Results indicate that, on average, producing 1 kg of biomass in this region uses 0.8 m 3 of water, and the green water footprint of producing 1 m 3 fuel is approximately 2150 m 3 water, or 57 m 3 water per GJ of energy, which is lower than reported values for wood‐based ethanol, sugar cane ethanol, and soybean biodiesel. Abstract : A watershed model is developed to predict and manage the water footprint of bioenergy feedstock production systems, specifically focusing on eucalyptus ( E. grandis ) plantations in Entre Rios, Argentina. Since fast‐growing bioenergy feedstocks like eucalyptus have high evapotranspiration rates, land use conversion is predicted to reduce streamflow; however, the model also predicts a range of biomass productivity across the watershed, enabling an approach to finding the best locations for feedstock development in terms of high productivity with least hydrologic impact. Results also indicate potential for a lower water footprint than for wood‐based ethanol, sugarcane ethanol, and soybean biodiesel.